Determination of seven phenolic acids in honey by counter flow salting-out homogeneous liquid–liquid extraction coupled with ultra-high performance liquid chromatography-tandem mass spectrometry. Issue 31 (26th July 2019) - Shi, Zhihong; Li, Xinye; Ma, Hongyu; Pang, Weiyue; Sun, Yamei; He, Yifan; Li, Meiting; Zhang, Hongyi
Abstract : CFSHLLE-UHPLC-MS/MS determination of phenolic acids in honey. Abstract : In this paper, counter flow salting-out homogeneous liquid–liquid extraction (CFSHLLE) was used for the determination of seven kinds of phenolic acids (PAs) in honey by ultra-high performance liquid chromatography-tandem mass spectrometry (UHPLC-MS/MS). In this method, an aqueous sample was mixed with an organic solvent and then the mixture was driven to pass through the salt layer. Owing to the salting-out effect, fine droplets of organic solvent formed at the interface of the salt layer and the aqueous sample, then rose up through the remaining mixture and aggregated as a separate layer on the top, thus the analytes were extracted into the organic phase. Phase separation occurs naturally without the assistance of centrifugation. Parameters affecting the extraction efficiency were optimized, such as the species and volume of extractant, the species and amount of salt, the flow rate and pH value. Appropriate linear ranges were obtained for the PAs with coefficients of determination between 0.9984 and 0.9998. The limits of detection were in the range of 1.6–63.9 ng g −1 . Relative standard deviations for intra-day ( n = 5) and inter-day ( n = 5) precision were lower than 5.51% and 7.65%, respectively. The proposed method proved to be simple, rapid, cost-effective and environmentally friendly. It has been successfully applied to the analysis of PAs in ten kinds of honey samples.